Hazard Level of Dengue Haemorrhagic Fever in Gorontalo Regency: Prediction of Spatial Distribution with AHP-GIS Integration - Ririn Pakaya; Yanti Hz Hano; Muhammad Ramdhan Olii (Al-Sihah : The Public Health Science Journal, 2021)
Under certain climatic conditions, Aedes aegypti and Aedes albopictus mosquitoes can survive and reproduce optimally so that climate change can significantly change the pattern of disease distribution. This study aimed to model the level of Dengue Haemorrhagic Fever (DHF) hazard in Gorontalo Regency by integrating the Analytical Hierarchy Process (AHP), Geographic Information System (GIS) with climatological and topographic factors. The factors that most influence the level of hazard of DHF are annual rainfall, altitude, and humidity. The results obtained show that Gorontalo Regency is dominated by the hazard level class of 94852.31 ha or 44.25% and the moderate class area of 82553.37 ha or 38.5% of the total area of Gorontalo Regency. These results prove that Gorontalo Regency is very at risk of DHF disease. If this is not handled by the government properly, the moderate class will potentially rise to the high class. The prediction model for the DHF hazard level in this study can be made according to local conditions in the research area which have limited data. Changes in climate variables and periodicity that affect the incidence of dengue can be flexibly adapted to this model. The findings from this study provide valuable insights that have the potential to improve mitigation in public health-related interventions.